Some issues of annual lump sum payments to combatants - Мekheda, Vladyslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
The purpose of the article is to analyze problematic issues regarding the type, purpose, functions, procedure for appointment, and amount of the annual one-time cash payment for the Independence Day of Ukraine to participants in hostilities and to make proposals for their resolution.The research methodology is based on a combination of systemic, comparative legal, and formal legal analysis aimed at identifying the content, type, purpose, and functions of social benefits in the system of social protection for war veterans.The work notes that the annual one-time cash payment to combatants, by its legal nature, is social assistance of an auxiliary nature, the purpose of which is to ensure comfortable conditions for their livelihoods.The annual lump sum payment performs a compensatory function, which consists in compensating for physical and moral stress associated with performing duties in particularly dangerous conditions.Based on the results of the study, it was concluded that it is advisable to devote a separate article to this payment in the Law of Ukraine «On the Status of War Veterans, Guarantees of Their Social Protection» dated October 22, 1993 No. 3551-XII, which would determine the legal nature, purpose, functions and fixed amount depending on the minimum pensions by age. Such proposals would comply with the principle of realism defined in the Strategy of Veteran Policy for the Period Until 2030 Strategy of Veteran Policy for the Period Until 2030, approved by the Order of the Cabinet of Ministers of Ukraine dated November 29, 2024 No. 1209-р.The author expresses the opinion that social justice and gratitude of society for the contribution of veterans to preserving Ukrainian statehood should become part of state policy. That is why the opinion of the judges of the Constitutional Court of Ukraine, set out in the Decision of February 27, 2020 No. 3-r/2020, that «…the state’s failure to fulfill social obligations towards war veterans, persons covered by Law No. 3551, undermines trust in the state… Limiting or canceling benefits for war veterans, persons covered by Law No. 3551, without their equivalent replacement or compensation is a violation of the state’s obligations regarding the social protection of persons who defended the Fatherland and their family members, is correct».